Vochysiaceae A. St.-Hil. na serra dos Pireneus, Goiás: diversidade e similaridade florística em áreas de cerrado no Brasil - Teixeira, Rayna Chaves (2017)
The Vochysiaceae family comprises about 240 species distributed in eight genera, six of which occur in the neotropical region (Callisthene Mart., Erisma Rudge, Qualea Aubl., Ruizterania Marc.-Berti, Salvertia A. St.-Hil., and Vochysia Aubl.) and two occur exclusively in Africa (Erismadelphus Mildbr. and Korupodendron Litt & Cheek). The family is known for presenting simple, opposing or verticillate leaves, zygomorphic flowers, isolated or arranged in thyrse, usually calcareous chalice, corolla with reduced number of petals (1, 3 or 5) and only a fertile stamen. This work was organized in two manuscripts with the objective of performing the taxonomic treatment of the Vochysiaceae occurring in the Serra dos Pireneus and also to evaluate the determinants of the diversity and floristic similarity of Vochysiaceae in areas of the Cerrado biome in Brazil. For the first manuscript, botanical material was collected fortnightly for one year in the Serra dos Pireneus. Materials deposited in the herbaria (CEN, ESA, GUA, HEPH, HRB, HUEFS, HUEG, HUFU, IBGE, K, MBM, MO, NY, RB, UB, UEC, UFG, US) were also examined by means of loans. The material collected was incorporated into the collection of the UFG herbarium and all the material examined was identified or had its identification revised. For the taxonomic treatment of the Vochysiaceae of the Serra dos Pireneus, morphological descriptions, taxonomic comments and geographic distribution of all taxa were produced. An identification key was also made for the taxa as well as illustrations. For the second manuscript, 14 surveys of Vochysiaceae were selected in different locations in the Cerrado. With the compilation of the data, the relative and independent importance of the geographic distance and altitude in the determination of the floristic similarity of Vochysiaceae between localities in the biome was evaluated. The Jaccard index was used to calculate the floristic similarity between the pairs of areas and the Mantel Partial Test to evaluate the correlation between the variables and the floristic similarity of Vochysiaceae independently. The study showed that altitude is more important than distance in predicting the extent to which the composition of Vochysiaceae varies between areas in the Cerrado.